A dynamic framework for managing customer engagement on social media / Muhammad Khairul Adli Ahmadie - Ahmadie, Muhammad Khairul Adli (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
This article is about a multi-actor engagement viewpoint that leads to ongoing contacts beyond the organization's network and traditional and discrete interactions between the organization and a single consumer to the understanding of customer engagement on social media. For businesses of all sizes, social media marketing is a great method to reach out to prospects and customers. People use social media to discover, learn about follow, and shop from brands. Great social media marketing may help your company achieve extraordinary success by cultivating loyal brand advocates and even driving leads and sales. Moreover, social media marketing is a type of digital marketing that makes use of the popularity of social media networks to reach marketing and branding objectives. Based on the article, the researchers explained that social media has evolved into a pervasive communication tool, allowing customers to interact and communicate with one another. According to Jaakkola & Alexander (2014) and Larivière et al (2017), social media have transformed simple dyadic interactions between customers and marketers into more complicated interactions involving various numerous groups of actors, such as customers, organisations, stakeholders, and non-customers.